IMPELEMNTATION OF SHARIA PRINCIPLES ON NOOR BANDUNG HOTEL MANAGEMENT - Yunita Utami Rahayu; Nurazizah Nurazizah; Denna Alfianita (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2020)
Sharia hotels are hotels that are managed in accordance with sharia principles, namely hotels that provide lodging, dining and drinking services and other services to the public, are managed commercially, and meet the conditions set by the National Sharia Council MUI No. 108 / DSN-MUI / X / 2016 concerning Guidelines for Organizing Tourism Based on Sharia Principles. One of the Sharia-based hotels in the Bandung area is the Noor Bandung Syariah Hotel, which is a hotel that implements Islamic Sharia into hotel operations. The formulation of the problem in this research is how the application of sharia principles in the Noor Hotel Syariah Bandung and how to service consumers at the Noor Hotel Syariah Bandung. This study aims to determine the application of sharia principles in the Noor Bandung Syariah Hotel and to find out services to consumers in the Noor Bandung Syariah Hotel. The method of this article was compiled using the Literature method and analyzed descriptively. In carrying out its operations at the Noor Hotel Syariah Hotel, Bandung has implemented the sharia principle very well, as well as the customer service that is in accordance with what should be done.